1988
DOI: 10.1002/ijc.2910420406
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of the EGF receptor and c‐myc genes in human esophageal cancers

Abstract: The incidence of esophageal cancer is extremely high in Linxian County and certain other regions of the People's Republic of China. Epidemiologic and laboratory studies suggest that N-nitroso carcinogens and other environmental factors play a causative role. In the present study, employing over 100 DNA samples obtained from Lin-xian patients who underwent surgery for esophageal cancer, we have found a significant frequency of amplification of either the human epidermal growth factor receptor (HER-I) gene or th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
57
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(58 citation statements)
references
References 19 publications
1
57
0
Order By: Relevance
“…Autocrine survival factors may also protect the tumor cells from chemotherapeutic drugs. Secretion of TGF a/EGF and overexpression of EGF receptors were not only reported in human esophageal carcinoma cell lines, but were also detected in human esophageal carcinoma tissues (Lu et al, 1988;Ozawa et al, 1987Ozawa et al, , 1989. In fact, the prognosis is poorer in esophageal cancer patients whose tumors express a higher level of EGF receptors (Iihara et al, 1993;Ozawa et al, 1989).…”
Section: Discussionmentioning
confidence: 96%
“…Autocrine survival factors may also protect the tumor cells from chemotherapeutic drugs. Secretion of TGF a/EGF and overexpression of EGF receptors were not only reported in human esophageal carcinoma cell lines, but were also detected in human esophageal carcinoma tissues (Lu et al, 1988;Ozawa et al, 1987Ozawa et al, , 1989. In fact, the prognosis is poorer in esophageal cancer patients whose tumors express a higher level of EGF receptors (Iihara et al, 1993;Ozawa et al, 1989).…”
Section: Discussionmentioning
confidence: 96%
“…[16][17][18][19] Epigenetic events, which are important in normal cellular functions, are also critical factors during initiation and progression of cancer. 20,21 Although genetic abnormalities in several oncogenes and tumor suppressor genes frequently occur in tumorigenesis, [22][23][24] our previous study showed that ECRG4 mRNA was downregulated with gene promoter hypermethylation in ESCC. 8 Tumor suppressor genes such as p14, p15, p16, FHIT, CDH1, MGMT, VHL, RASSF1A and E-cadherin are usually downregulated by gene promoter hypermethylation in ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…Especially in ESCC, oncogenes, such as SMYD2 (1q32.3-q41), EGFR (7p12), MYC (8q24.21), CCND1 (11q13), cIAP1 (11q22) and ERBB2 (17q21.1), have already been identified as major amplification targets associated with development, progression and metastasis of aggressive disease (Lu et al, 1988;Imoto et al, 2001;Jain et al, 2007;Komatsu et al, 2009;Sato-Kuwabara et al, 2009). Among them, CCND1 is the gene most frequently amplified (22 -65%) with high copy numbers, and also associated with a poorer survival outcome in ESCC patients (Lam, 2000).…”
Section: Discussionmentioning
confidence: 99%